India and Japan Assessing the Strategic Partnership (Politics of South Asia,, 2018)
This volume focuses on the rapidly expanding strategic relationship between India and Japan, expanding on the hitherto under-analyzed concept of "strategic partnership," tracing the history of the interaction, and gauging its current and future trajectories. The rise of China and its challenge to U.S. dominance of the global system is the setting in which the partnership has assumed a major profile, incorporating both defence and economic cooperation on an unprecedented scale. The increasing congruence of Indian and Japanese interests is juxtaposed with the inherent limitations of the partnership to portray a complex picture of a kind of strategic relationship that has become a staple of contemporary international politics. Rajesh Basrur is Professor of International Relations and Coordinator of the South Asia Programme at the S. Rajaratnam School of International Studies, Nanyang Technological University, Singapore. He has authored five books, most recently (with Kate Sullivan De Estrada) Rising India: Status and Power (2017). Sumitha Narayanan Kutty is Associate Research Fellow, South Asia Programme at the S. Rajaratnam School of International Studies, Nanyang Technological University, Singapore. Her work has appeared in several publications including The Washington Quarterly and Asia Policy.